Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/spectrum.00453-21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candidemia in Children over 7 Years in a Medical Center in Turkey

Abstract: In our study, the changing epidemiology of Candida species in candidemia in children was evaluated. The dominance of Candida parapsilosis species in the changing epidemiology was remarkable. We found that fluconazole resistance was high in both parapsilosis and nonparapsilosis groups. Updating local epidemiologic data at certain intervals in candidemia cases is important in determining both the changing epidemiology and empirical antifungal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Candidaalbicans was the most prevalent species, followed by C. parapsilosis among candidemia patients, according to many reports in the literature (6,9). On the contrary, C. parapsilosis has been reported as the most commonly isolated Candida strain in other studies (10,11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Candidaalbicans was the most prevalent species, followed by C. parapsilosis among candidemia patients, according to many reports in the literature (6,9). On the contrary, C. parapsilosis has been reported as the most commonly isolated Candida strain in other studies (10,11).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, 57% of the patients were hospitalized in the intensive care unit. The incidence rate reported from Turkey in the literature ranges from 0.56 to 11.5 per 1000 admissions (1,10,16,17). The literature data indicated that ICU patients had higher candidemia risk and mortality than general ward patients (4).…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B resistance was found in 1.3% of all isolates. Ciftdogan et al 35 reported that out of 71 C. parapsilosis isolates in children with candidemia, 33.8% were resistant to fluconazole. We detected fluconazole resistance in 9.5% of CA isolates, which was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B resistance was found in 1.3% of all isolates. Ciftdogan et al35 reported that out of 71 C. parapsilosis isolates in children with…”
mentioning
confidence: 99%
“…Candidemia is an important opportunistic infection in pediatric populations at risk, mainly neonates and those with hematologic malignancies [ 42 ] and patients in mechanical ventilatory support and immunosuppressive therapy [ 43 ]. However, risk factors for candidemia may vary according to patient populations and fungal etiology, which brings challenges to clinical diagnosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%